Identification of New Aquaporin Genes and Single Nucleotide Polymorphism in Bread Wheat. (January 2013) - Pandey, B.; Sharma, P.; Pandey, D.M.; Sharma, I.; Chatrath, R.
Major facilitators of water movement through plant cell membranes include aquaporin proteins. Wheat is among the largest and most important cereal crops worldwide; however, unlike other model plants such as rice, maize and Arabidopsis, little has been reported on wheat major intrinsic proteins (MIPs). This study presents a comprehensive computational identification of 349 new wheat expressed sequence tags (ESTs), encoding 13 wheat aquaporin genes. Identified aquaporins consist of 6 plasma membrane intrinsic proteins (PIP) and 1 TIP showing high sequence similarity with rice aquaporins. We also identified 4 NOD26-like intrinsic proteins (NIP) and 2 SIP members that showed more divergence. Further, expression analysis of the aquaporin genes using the available EST information in UniGene revealed their transcripts were differentially regulated in various stress- and tissue-specific libraries. Allele specific Polymerase chain reaction (PCR) primers based on single nucleotide polymorphism (SNP) were designed using PIP as the target gene and validated on a core set of Indian wheat genotypes. A 3D theoretical model of the wheat aquaporin protein was built by homology modeling and could prove to be useful in the further functional characterization of this protein. Collectively with expression and bioinformatics analysis, our results support the idea that the genes identified in this study signify an important genetic resource providing potential targets to modify the water use properties of wheat.